2022
DOI: 10.1021/acsanm.1c04348
|View full text |Cite
|
Sign up to set email alerts
|

EDTA–Fe2+ Complex-Functionalized Fe3O4 Nanozyme as Tyrosine Hydroxylase Mimics for the Production of l-DOPA

Abstract: l-3,4-Dihydroxyphenylalanine (l-DOPA) is widely used in the treatment of Parkinson’s disease. Fe3O4 magnetic nanoparticles decorated with ethylenediaminetetraacetic acid (EDTA)–Fe2+ complexes were developed as nanozymes for the biomimetic synthesis of l-DOPA by mimicking tyrosine hydroxylase. The nanozyme was synthesized by anchoring Fe2+ ions onto EDTA-grafted Fe3O4 magnetic nanoparticles. Scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier-transform infrared, X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…After a laborious workup, the product of hydroxylation at position C3 in the aromatic ring, i.e., levodopa, was obtained, which was proven by extracting and analyzing this product from the reaction mixture. There are also other examples of metal-catalyzed oxidation of l -tyrosine, l -phenylalanine, and 2-phenylethylamine that rationalize the hypothesis of mono- and dihydroxylation as the first initial step of the proposed polymerization. All of these suggest, in this condition, that the hydroxylation of the aromatic ring occurs, and then the oxidative polymerization of levodopa may occur with a similar mechanism to dopamine (Scheme , R = CO 2 H). It is likely that both l -phenylalanine and 2-phenylethylamine may undergo a similar mechanism.…”
Section: Mechanismmentioning
confidence: 85%
“…After a laborious workup, the product of hydroxylation at position C3 in the aromatic ring, i.e., levodopa, was obtained, which was proven by extracting and analyzing this product from the reaction mixture. There are also other examples of metal-catalyzed oxidation of l -tyrosine, l -phenylalanine, and 2-phenylethylamine that rationalize the hypothesis of mono- and dihydroxylation as the first initial step of the proposed polymerization. All of these suggest, in this condition, that the hydroxylation of the aromatic ring occurs, and then the oxidative polymerization of levodopa may occur with a similar mechanism to dopamine (Scheme , R = CO 2 H). It is likely that both l -phenylalanine and 2-phenylethylamine may undergo a similar mechanism.…”
Section: Mechanismmentioning
confidence: 85%
“…The results were consistent with previous researches. [ 17,18 ] HPLC, Arnow assay, NBT assay, and ethylenediamine assay indicated that a part of tyrosine residues of fibroin was successfully transformed into DOPA residues (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, a biomimetic synthesis method was developed to convert tyrosine to DOPA by mimicking tyrosine hydroxylase, in which complex between Fe 2+ and ethylenediaminetetraacetic acid (EDTA) performed as active site with H 2 O 2 as oxygen donor and ascorbic acid as reducing agent. [17,18] This biomimetic synthesis method had the advantages of quick reaction and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Iron-based catalysts have been reported to catalyze the hydroxylation of tyrosine and achieve high catalytic conversion 24 , 25 . Based on the further investigation of nanozymes, we proved that Fe 3 O 4 could generate Fe(IV)=O active intermediates.…”
Section: Discussionmentioning
confidence: 99%